Factors Affecting COVID-19 Outcomes in Cancer Patients: A First Report From Guy's Cancer Center in London - Russell, Beth; Moss, Charlotte; Papa, Sophie; Irshad, Sheeba; Ross, Paul; Spicer, James; Kordasti, Shahram; Crawley, Danielle; Wylie, Harriet; Cahill, Fidelma; Haire, Anna; Zaki, Kamarul; et al. (Frontiers in Oncology, 2020)
Background: There is insufficient evidence to support clinical decision-making for cancer patients diagnosed with COVID-19 due to the lack of large studies. Methods: We used data from a single large UK Cancer Centre to assess demographic/clinical characteristics of 156 cancer patients with a confirmed COVID-19 diagnosis between 29 February-12 May 2020. Logistic/Cox proportional hazards models were used to identify which demographic and/or clinical characteristics were associated with COVID-19 severity/death. Results: 128 (82%) presented with mild/moderate COVID-19 and 28 (18%) with severe disease. Initial diagnosis of cancer >24months before COVID-19 (OR:1.74 (95%CI: 0.71-4.26)), presenting with fever (6.21 (1.76-21.99)), dyspnoea (2.60 (1.00-6.76)), gastro-intestinal symptoms (7.38 (2.71-20.16)), or higher levels of CRP (9.43 (0.73-121.12)) were linked with greater COVID-19 severity. During median follow-up of 37days, 34 patients had died of COVID-19 (22%). Asian ethnicity (3.73 (1.28-10.91), palliative treatment (5.74 (1.15-28.79), initial diagnosis of cancer >24monhts before (2.14 (1.04-4.44), dyspnoea (4.94 (1.99-12.25), and increased CRP levels (10.35 (1.05-52.21)) were positively associated with COVID-19 death. An inverse association was observed with increased levels of albumin (0.04 (0.01-0.04). Conclusions: A longer-established diagnosis of cancer was associated with increasing severity of infection as well as COVID-19 death, possibly reflecting effects of more advanced malignant disease impact on this infection. Asian ethnicity and palliative treatment were also associated with COVID-19 death in cancer patients.